Sudden death in sport and riding horses during and immediately after exercise: A case series. (5th February 2018) - de Solis, C. Navas; Althaus, F.; Basieux, N.; Burger, D.
Summary: Background: Sudden death affects the health of horses, the safety of riders and the public perception of animal welfare during equestrian events. Objectives: To describe the signalment, clinical history, sudden death episode, rider injuries and causes of sudden death during exercise or closely thereafter in sport and pleasure riding horses. Study design: Retrospective case series based on an online questionnaire. Methods: An online questionnaire was distributed to the veterinary and equestrian community. Connections of animals reported in the press to have died suddenly were sent the survey. Responses were analysed to obtain information. Results: Fifty‐seven cases met inclusion criteria with enough information to be analysed. The most common discipline was eventing (n = 23, 40.4%), and the most common breed involved was Thoroughbred (n = 23, 40.4%). Forty‐one (71.9%) horses collapsed during exercise, and 16 (28.1%) shortly thereafter. Twenty‐four (42.1%) horses died during or near the time of competition and 33 (57.9%) during or near the time of training or a pleasure ride. In 16 (28.1%) horses, the cause of death was known or strongly suspected based on a post‐mortem result, and a cardiovascular origin was reported in 13 of these 16 cases. Riders were injured in 13 (22.8%) cases, and injuries to their extremities were the most frequent. Main limitations: There is potential for misdiagnosis and recall and selection bias, and in the absence of data on the total number of horses engaged in equestrian sports and riding, prevalence cannot be calculated. Conclusions: Sudden death occurred in many types of equestrian sports and in riding horses. Death outside competition was more common suggesting that registries based on reports from official veterinarians underestimate the magnitude of this problem. Rider injuries were not uncommon when ridden horses collapsed and died. A definitive diagnosis for the cause of death was not commonly achieved and cardiovascular origin was the most common where a diagnosis was proposed by survey respondents.